Exports and Economic Growth: The Causality Test for ASEAN Countries - Abdul Ghafar Ismail; D. Agus Harjito (Economic Journal of Emerging Markets, 2003)
This study proposes to investigate the causality between exports and economic growth in the ASEAN countries over the periods 1966 –2000. The role of the export variable in the investigation of economic growth is emphasized. Using the Johansen cointegration procedures test indicate that there is cointegration between export and economic growth in Indonesia and Singapore, while the Granger causality test shows that there is feedback or bi-directional causality between exports and economic growth only in Indonesia and Philippines. JEL classification: C22; F14; F43;Keywords: export; economic growth; cointegration; causality test.